ANALISIS EKUITAS MEREK (BRAND EQUITY) SEPEDA MOTOR HONDA DI SUKABUMI - Hesti Nuramdini; Gita Sagita; Dewi Herawati; Bunyana Bunyana; Ce Gunawan (Marketgram Journal, 2023)
The purpose of this study was to determine the level of brand equity of Honda motorcycles in Sukabumi as measured through the dimensions of brand equity as follows: a. Brand Awareness b Perceived Quality c. Brand Association and Brand Loyalty. The research method uses descriptive quantitative methods. The purpose of this study is to describe something characteristic of a person, event or situation. The data source used in this study is primary data, the data collection method is carried out by distributing questionnaires. The sample used is 109 respondents who use Honda motorcycles in Sukabumi. The results showed that the brand awareness of Honda motorcycles was in the high category. Judging from the quality of Honda motorcycles, they are in the very high category. The Honda motorcycle brand association is in the high category. The brand loyalty of Honda motorbikes is in the high category.